PHYTOCHEMICAL CHARACTERIZATION AND TANNIN STABILITY TEST FROM KLUWEK (Pangium edule Reinw) - Warnasih, Siti; Hasanah, Uswatun (Universitas Pakuan, 2018)
One of the herbs that can be used as a source of natural dye is the kluwek which is brown. This study aims to determine the type of secondary metabolite compounds producing color, and to determine the stability of tannin in various conditions such as pH, oxidizing, UV rays, heating temperature, and storage using UV-Vis spectrophotometry method. This research includes preparation of kluwek, extraction with acetone:water (7:3) with maceration method, phytochemical test (tannin, flavonoid, carotenoid, and anthocyanin) and total tannins, and tannin stability test on various pH, oxidizing, UV rays, temperature and duration of heating, and storage using the UV-Vis spectrophotometry method. The results obtained are kluwek extract containing tannin, flavonoid, carotenoid, and anthocyanin compounds, and total tannins 2.80%. Based on the tannin content, kluwek extract stable at pH 6-7, heating 60-80 oC, and storage up to 9 days at temperature 27 °C, and kluwek extract unstable when contact with 1% H2O2, UV light, and if kept at cold temperature (10 ˚C).